2015
DOI: 10.4236/msa.2015.610088
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organoclay Structure on Nanostructured Materials Based on Eva

Abstract: This article reports the preparation of a series of EVA nanocomposites employing solution casting methods using different types of organo-modified montmorillonite clay. The effect of the organoclay type on the structural organization and thermal behavior of EVA nanostructured materials were systematically investigated. Regarding thermal behavior, the thermogravimetric analysis showed that the nanocomposites presented a slight decrease in thermal degradation temperature compared to EVA, while differential scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…[22] Compared with sodium-based MMT, the lamellar spacing is enlarged, and the presence of the intercalated portion was identified from the shift in the d (001) peak to lower angles, indicating an increase in basal distance as a consequence of the interpenetration of LDH inside the MMT lamellae. [35] This result is in line with the periodic alternating arrangement of LDH and MMT shown in Figure 3C, D Furthermore, there are no (003) reflection peaks of LDH in the pattern of LM, indicating that the layered structure of LDH is not entirely formed because the formamide weakens the interactions between neighboring layers and prevents interlayer growth. [36] All the above results suggest that the hybrid with a periodically alternating layered structure can be obtained by depositing LDH on the surface of exfoliated MMT nanosheets.…”
Section: Structure and Morphologysupporting
confidence: 80%
“…[22] Compared with sodium-based MMT, the lamellar spacing is enlarged, and the presence of the intercalated portion was identified from the shift in the d (001) peak to lower angles, indicating an increase in basal distance as a consequence of the interpenetration of LDH inside the MMT lamellae. [35] This result is in line with the periodic alternating arrangement of LDH and MMT shown in Figure 3C, D Furthermore, there are no (003) reflection peaks of LDH in the pattern of LM, indicating that the layered structure of LDH is not entirely formed because the formamide weakens the interactions between neighboring layers and prevents interlayer growth. [36] All the above results suggest that the hybrid with a periodically alternating layered structure can be obtained by depositing LDH on the surface of exfoliated MMT nanosheets.…”
Section: Structure and Morphologysupporting
confidence: 80%
“…The spin-lattice relaxation data of the systems containing modified nanoparticle, presented differences in relation to the EVA/ZnO systems with 0.25% and 0.5%. In both systems, the nanoparticle modification led to T 1.1 H increase, elucidating decrease of the molecular mobility of the polymer along with the increase of the polymer-nanoparticle interaction and indicating greater dispersion of the oxide in the amorphous area of the material [47] [48] [49], where there is no variation of the percentage of T 1,2 H with nanoparticle modification. These data corroborate the results of DMA, where the analysis indicated that the modification induced an increase in the polymer-nanoparticle interactions.…”
Section: Time Domain Nuclear Magnetic Resonancementioning
confidence: 99%
“…Generally speaking, the decrease in the proton spin-lattice relaxation time comes from the clay lamellae's exfoliation because the presence of paramagnetic metals in the presence of clay structure interferes in the near proton relaxation mechanism. The contrary effect in proton relaxation time is expected for the samples containing polymer chains intercalated in the clay lamellae because of the restriction of their molecular mobility [7]- [12].…”
mentioning
confidence: 91%